Pengembangan Kompetensi Manajemen Layanan Bimbingan Dan Konseling Menggunakan Classpoint Pada Guru BK Di Palangka Raya - Esty Pan Pangesty; Romiaty Romiaty; Nofi Feronika; Mimi Suratie; Oktamia Karuniaty Sangalang (Universitas Tanjungpura, 2023)
Guidance and counseling cannot be separated from the influence of advances in information technology. This means that in the planning process, the activity reaches the evaluation and follow-up stage of the guidance and counseling service activities to use information technology. One of the counseling services that cannot be separated from technological advances is information services. One application that can generate student activity and participation is the classpoint application. The classpoint application is a media that is integrated with Microsoft PowerPoint which in its application encourages interactions that occur between the presenter and the audience. The objectives of community service for those carried out at Palangka Raya State Junior High School are, 1) To find out the description of the ability of BK teachers in Palangka Raya in utilizing information technology. 2). To develop a training design for using the Classpoint Application for BK teachers in Palangka Raya. 3). To see the effectiveness of training on the use of the Classpoint Application for BK teachers in Palangka Raya. The method used in community service is by using a participatory action research (PAR) model. PAR is research to define a problem or apply information into action as a solution to a problem that has been defined. The principle of PAR implementation uses the to know, to understanding, to plan, to action and to reflection (KUPAR) cycle. The details of service activities in each of the steps are as follows, 1). To find out, it is done by identifying problems in the use of IT media in making BK media. 2). To Plan where researchers and communities plan actions to review plans from various relevant sources such as books and research articles to solve problems with the most effective and efficient solutions. 3). Actions where the researcher implements the plan that has been planned in the previous step, 4). Reflection where researchers find and monitor actions that have been taken for reflection. The targeted outputs of this activity are videos uploaded on YouTube, scientific articles to be published in Sinta 4 accredited scientific journals, and IPR scientific articles.